2013
DOI: 10.1161/circulationaha.112.123653
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Heart Transplant Survival by Targeting the Ionotropic Purinergic Receptor P2X7

Abstract: Background Heart transplantation is a lifesaving procedure for patients with end-stage heart failure. Despite much effort and advances in the field, current immunosuppressive regimens are still associated with poor long-term cardiac allograft outcomes as well as with the development of complications including infections and malignancies. The development of a novel, short-term and effective immunomodulatory protocol will thus be an important achievement. The purine adenosine 5′-triphosphate (ATP), released duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
93
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(100 citation statements)
references
References 40 publications
7
93
0
Order By: Relevance
“…Lack of the P2X7R prevents GVHD (8) and P2X7R targeting increases long-term survival of heart and pancreatic islets transplants (9,10). Thus, we hypothesized that host P2X7R deletion might facilitate tumor progression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lack of the P2X7R prevents GVHD (8) and P2X7R targeting increases long-term survival of heart and pancreatic islets transplants (9,10). Thus, we hypothesized that host P2X7R deletion might facilitate tumor progression.…”
Section: Resultsmentioning
confidence: 99%
“…6, 7), thus the question arises as to what extent host P2X7R is needed to control tumor growth, and whether P2X7R blockade might impair the antitumor immune response. Previous studies show that genetic deletion of P2X7R prevents GVHD (8), and that P2X7R blockade prevents rejection of allogeneic transplants (9,10).…”
Section: Introductionmentioning
confidence: 98%
“…There was significant reduction of ATP levels in 1-day-old blood compared to fresh blood, suggesting that fresh blood should be used for assessing T cell immune function in transplant patients [783]. A recent study found that P2X7R are specifically upregulated in graft-infiltrating lymphocytes in cardiactransplanted humans and mice [784]. Furthermore, a shortterm treatment with a P2XR antagonist prolonged cardiac transplant survival [784].…”
Section: Heart Transplantationmentioning
confidence: 99%
“…A recent study found that P2X7R are specifically upregulated in graft-infiltrating lymphocytes in cardiactransplanted humans and mice [784]. Furthermore, a shortterm treatment with a P2XR antagonist prolonged cardiac transplant survival [784].…”
Section: Heart Transplantationmentioning
confidence: 99%
“…Studies in transplantation have shown upregulation of P2X7 expression on infiltrating lymphocytes in transplanted hearts in human patients [106] . Pharmacological blockade and genetic deletion of P2X7 in murine models leads to a delay in allograft rejection, which has been demonstrated in several transplant models including models of islet [107] , heart [106] and lung [108] transplantation. However, with the exception of one preliminary report [109] , there are limited studies investigating P2X7 in skin transplants.…”
Section: Skin Transplantationmentioning
confidence: 99%